Immunohistochemistry of thrombi following iliac venous stenting: A novel model of venous thrombosis - Burches, Bobby; Karnicki, Krzysztof; Wysokinski, Waldemar; McBane, Robert D., II (Thrombosis and Haemostasis, 2006)
Stenting has become a common intervention for venous occlusive disease. Little is known regarding the composition of venous thrombi complicating stent placement. The optimal design of antithrombotic agents in this setting requires this knowledge. Quantitative immunohistochemistry was undertaken to define the platelet, fibrin(ogen) and leukocyte composition and spatial orientation of venous thrombi following percutaneous iliac stent placement in pigs. Venous stent thrombus size was measured by weight and scintillation detection of autologous 111In-platelets. Thrombi were divided in segments (cephalad to caudad), sectioned and stained with monoclonal anti-platelet glycoprotein Ib or polyclonal anti-fibrin(ogen) fluorescent antibodies. Thrombus platelet content was 100-fold greater than paired whole blood samples. The caudal-most segments contained platelet-rich aggregates (p<0.05) with abundant leukocytes (p<0.0001) relative to more cephalad segments. Platelet and fibrin(ogen) content varied over an eight-fold range between segments but were directly correlated with each other (r=0.77; p<0.0001). The platelet co-localization with fibrin(ogen) is consistent with the phospholipid dependence of prothrombin activation. The abundance and caudal distribution of platelet-leukocyte aggregates indicate their preferential accretion from flowing blood early in the genesis of venous stent thrombi. These may represent novel cellular targets for the prevention and treatment of venous thrombosis.
Keywords: Venous thrombosis; vascular stents; platelets